To Help or not to Help: The Samaritan's Dilemma Revisited - Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1999)
Helping somebody may undermine his incentives to work. What Buchanan identified more than 25 years ago as the Samaritan's dilemma is basically a time-inconsistency problem. The paper discusses possible solutions of the dilemma such as punishment within an iterated game, reshaping the game in the direction of a dynamic one-shot game and the delegation of the power of decision to an agent. The paper shows that only the latter option works. – – Jemandem Hilfe zukommen zu lassen verwässert seine Arbeitsanreize. Was Buchanan vor über 25 Jahren als Samariter-Dilemma identifiziert hat, ist im Grunde ein Zeit-Inkonsistenz-Problem. Der Beitrag diskutiert mögliche Auswege aus dem Dilemma, etwa Bestrafungen innerhalb eines wiederholten Spiels, Änderung der Spielstruktur in Richtung eines dynamischen Einmal-Spiels und die Delegierung der Entscheidungsmacht an einen Agenten. Es wird gezeigt, dass nur die letztere Möglichkeit das Dilemma löst.
Keywords: C72; 330; Samaritan's Dilemma; Game Theory; Altruismus; Spieltheorie; Zeitkonsistenz; Theorie